Pengaruh Harga dan Kualitas Produk Terhadap Kepuasan Konsumen Brand Skincare Halal: Studi Kasus: Mahasiswa Kampus Kemandirian Sidoarjo - Diah Oktaviani; Saifuddin Saifuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid growth of the halal skincare industry in Indonesia has triggered increasingly fierce competition among brands. This phenomenon pressures companies to develop competitive pricing strategies while maintaining superior product quality, with the aim of achieving optimal consumer satisfaction. Consumer satisfaction is a crucial factor because it directly influences customer loyalty and continued product usage. This study focuses on students at the Kemandiri Campus in Sidoarjo as research subjects. This group represents young, critical, rational consumers with a high awareness of Islamic values. As members of an Islamic educational institution, they tend to prioritize halal aspects, superior quality, and affordable prices when choosing skincare products. Furthermore, the increasing demand among students for safe, economical, and sharia-compliant skincare products makes halal skincare a contextually relevant research topic. This study aims to examine the influence of price and product quality on consumer satisfaction with halal skincare products among students at the Kemandiri Campus in Sidoarjo. A quantitative approach was applied, involving 100 respondents selected through purposive sampling. Data were collected through a questionnaire, followed by validity, reliability, and classical assumption tests, with hypothesis testing using the F test and t test. The results showed a t probability value of 0.001 for price and 0.000 for quality (both <5%), thus proving a significant positive influence.